2007
DOI: 10.2174/138920307780831857
|View full text |Cite
|
Sign up to set email alerts
|

The PYRIN Domain in Signal Transduction

Abstract: The Death Domain Fold superfamily of evolutionarily conserved protein-protein interaction domains consists of 4 subfamilies: the death domain, the death effector domain, the caspase recruitment domain, and the PYRIN domain. Interaction of Death Domain Fold containing proteins modulates the activity of several downstream effectors, such as caspases and transcription factors. Recent studies provide evidence for not only homotypic-, but also heterotypic interactions among different sub-families, and even unconven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
21
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 213 publications
(357 reference statements)
0
21
0
1
Order By: Relevance
“…The PYD, also referred to as PAAD or DAPIN, is a protein binding domain belonging to the death domain superfamily (12). The structure of several PYDs has been determined, which revealed a bundle of 5- to 6-α-helices.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The PYD, also referred to as PAAD or DAPIN, is a protein binding domain belonging to the death domain superfamily (12). The structure of several PYDs has been determined, which revealed a bundle of 5- to 6-α-helices.…”
Section: Introductionmentioning
confidence: 99%
“…However, the precise function of most family members is still unknown (3639). Besides NLRPs and ALRs, the PYD is also present in the inflammasome adaptor protein ASC, the regulatory PYD-only proteins (POPs) and Pyrin (Figure 1C) (12). Below, we will specifically discuss the mechanism of activation and function of NLRPs and ALRs, and how defects within these proteins are involved in immune-related disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Instead, the MYXV-encoded protein M013, which was first identified as a member of the PYRIN domain (PYD) superfamily, was shown to function as an intracellular inhibitor of inflammasome activation [33]. The cellular PYD-containing proteins mediate protein-protein interactions with components of signaling pathways involved in the regulation of apoptosis, NF-κB activation and pro-inflammatory cytokine production [34],[35]. Our initial study showed that a MYXV construct deleted for M013L (vMyxM013-KO) was significantly attenuated in host rabbits because of decreased virus dissemination and enhanced inflammatory responses at the tissue sites of virus infection [33].…”
Section: Introductionmentioning
confidence: 99%
“…FMF'e neden olan gen MEFV geni (Mediterranean Fever Gene) 16 numaralı kromozomda lokalize olup (16p13,3) 10 ekzona sahiptir ve 781 aminoasitlik pirin adı verilen bir proteini kodlar. Pirin, apopitotik ve inflamatuvar sinyal yolunda fonksiyonu olduğu düşünülen bir proteindir [6][7][8]. MEFV geninin ürünü olan pirin proteini interlökin 1β üretimini inhibe eder.…”
Section: Introductionunclassified